HUBUNGAN LAMA MENGIDAP KUSTA DENGAN TINGKAT DEPRESI PADA PASIEN DI RUMAH SAKIT KUSTA SUMBERGLAGAH KABUPATEN MOJOKERTO - Widya Ayu Putri Maharani; Ida Srisurani Wiji Astuti; Justina Evy Tyaswati (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Leprosy is a chronic infection disease that caused by Mycobacterium leprae and oftentimes causing negative stigma for people infected by it. The negative stigma and the life quality degradation in people with leprosy lead to the higher risk of depression than people without this disease. Depression is a period of disruption of human function associated with sadness feeling, included changes in sleep pattern and appetite, psychomotor, concentration, anhedonia, fatigue, feeling hopeless, helpless, and having suicidal thoughts. The risk of depression will increase about 2,6 times in people who have chronic illness, one of which is leprosy. This was an analytic observational study with cross sectional approach using 60 respondents chosen by purposive sampling technique. Data were obtained through interview using Hamilton Depression Rating Scale (HDRS) questionnaire and analyzed using Spearman correlation test (p<0,05). The results showed that most respondents (36,7%) suffered from leprosy for 0-14 year(s), in which 51,7% had no depression, 38,3% had mild depression, 16,7% had moderate depression, and 3,3% had severe depression. The analytic results showed the significance value of (p) 0,025 and correlation coefficient of (r) 0,290. It could be concluded that there is a correlation between the duration of leprosy and level of depression in patients at Sumberglagah Leprosy Hospital Mojokerto District with weak correlation strength and positive correlation value so it means that the longer the patient suffering from leprosy, the higher the depression level and likewise on the contrary.